2010
DOI: 10.1111/j.1365-2613.2009.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of CXCL10 in the induction of cell injury and mitochondrial dysfunction

Abstract: Chemokines have been known to play a critical role in pathogenesis of chronic pancreatitis and acinar cell death. However, the role played by one of the CXC chemokines: CXCL10 in regulation of acinar cell death has remained unexplored. Hence, this study was designed to assess the role of CXCL10 promoting apoptosis in ex vivo cultured acinar cells. Primary human pancreatic acinar cell cultures were established and exposed to varying doses of CXCL10 for different time intervals. Apoptotic induction was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…23 CXCR3 is coupled to a G-protein signaling pathway with its downstream protein p38-MAPK. [23][24][25][26] It has been reported that CXCL10 can trigger apoptosis in several normal cellular models, such as acinar cells, 27 neurons, 28 microvascular endothelial cells, 29 and recently blood T lymphocytes. 26 However, the apoptosis pathway of CXCR3 is not yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…23 CXCR3 is coupled to a G-protein signaling pathway with its downstream protein p38-MAPK. [23][24][25][26] It has been reported that CXCL10 can trigger apoptosis in several normal cellular models, such as acinar cells, 27 neurons, 28 microvascular endothelial cells, 29 and recently blood T lymphocytes. 26 However, the apoptosis pathway of CXCR3 is not yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we could functionally link these two observations and show that an increase of apoptotic cells within livers of HCV‐infected patients is strongly correlated with an increased mRNA expression of CXCL10. These findings, together with the knowledge of the involvement of CXCL10 in epithelial,16 pancreatic,15 and β‐cell14 injury, motivated our interest to further understand the role of CXCL10 in liver cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that CXCL10 might operate through a noncognate receptor and thereby mediate biological effects independent of CXCR3. Indeed, CXCL10 has been implicated in non‐chemokine‐receptor‐mediated apoptotic effects in cell culture 14‐16. However, whether these effects are also true for liver cells and whether they also operate in vivo have not yet been investigated.…”
mentioning
confidence: 99%
“…they affect cells by activating surface receptors, which are seven-transmembranedomain g-protein-coupled receptor (5). evidence suggest that members of this group are correlated with inflammatory reaction (6), injure recovery (7), cell proliferation (8,9), apoptosis (10) and one even involved the regulation of chemotherapeutic agent-induced apoptosis (11,12). cXcl12 increases resistance of small-cell lung cancer cells to chemotherapy by activation its receptor cXcr4 (13).…”
Section: Introductionmentioning
confidence: 99%